Analysis of coupler jackknifing and its effect on locomotives on a tangent track. (May 2018) - Guo, Lirong; Wang, Kaiyun
Coupler jackknifing has caused a number of derailments, and it is a significant topic that needs in-depth studies. This paper aims to investigate the characteristics of coupler jackknifing and its effects on the dynamic performance of locomotives during braking. A field braking experiment using three eight-axle locomotives was conducted on a tangent track. The experimental results indicated that in-service couplers with a friction arc surface are prone to coupler jackknifing once the compressive force of the coupler exceeds 400 kN. After coupler jackknifing, the coupler angle has a significant positive correlation with the yaw angle of the car body; both coupler jackknifing and coupler angle increase rapidly to maximum values. The contact between the car body and the bogie seriously affects the dynamic performance of the locomotive and causes lateral instability of the locomotive. In particular, the lateral deviation of the coupling couplers generates an eccentric wear on the tail of the coupler. A numerical simulation model is developed to investigate the effect of coupler jackknifing on the running safety of the locomotive. Simulation results show that coupler jackknifing induces an excessive lateral force on the wheelset and increases the risk of derailments and gauge widening. Compared with the existing measures against coupler jackknifing, in this study, an effectively active measure is proposed to improve the stability of the coupler and to prevent possible derailments caused by coupler jackknifing during braking.